Methods for Measuring the Concentrations of Proteins - Kielkopf, Clara L; Bauer, William; Urbatsch, Ina L (Cold Spring Harbor protocols, 2020)
Determining the concentration of protein samples generally is accomplished either by measuring the UV absorbance at 280 nm or by reacting the protein quantitatively with dyes and/or metal ions (Bradford, Lowry, or BCA assays). For purified proteins, UV absorbance remains the most popular method because it is fast, convenient, and reproducible; it does not consume the protein; and it requires no additional reagents, standards, or incubations. No method of protein concentration determination is perfect because each is subject to a different set of constraints such as interference of buffer components and contaminating proteins in direct UV determination ( ) or reactivity of individual proteins and buffer components with the detecting reagents in colorimetric assays. In cases in which protein concentration is critical (e.g., determination of catalytic rate constants for an enzyme), it may be advisable to compare the results of several assays.